2017
DOI: 10.1242/jeb.156935
|View full text |Cite
|
Sign up to set email alerts
|

Heat-resistant cytosolic malate dehydrogenases (cMDHs) of thermophilic intertidal snails (genus Echinolittorina): protein underpinnings of tolerance to body temperatures reaching 55°C

Abstract: Snails of the genus Echinolittorina are among the most heat-tolerant animals; they experience average body temperatures near 41-44°C in summer and withstand temperatures up to at least 55°C. Here, we demonstrate that heat stability of function (indexed by the MichaelisMenten constant of the cofactor NADH, K M NADH ) and structure (indexed by rate of denaturation) of cytosolic malate dehydrogenases (cMDHs) of two congeners (E. malaccana and E. radiata) exceeds values previously found for orthologs of this prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 62 publications
1
31
1
Order By: Relevance
“…Positively selected loci identified in this study provide opportunities to compare allele frequency patterns in multiple M. galloprovincialis populations to determine whether genes under selection for species divergence (identified in this study) are also important for local adaptation within species. Sequence data can also be used in combination with computational approaches to investigate how specific amino acid substitutions affect three‐dimensional protein structure and thermal stability, or whether these sites comprise binding regions undergoing large conformational changes during catalysis (e.g., Fields, Dong, Meng, & Somero, ; Fields et al, ; Liao et al, ; Saarman, Kober, Simison, & Pogson, ). Such data would allow a more direct assessment of the contributions of thermal selection on the evolution of species characteristics mediating present‐day distribution limits.…”
Section: Discussionmentioning
confidence: 99%
“…Positively selected loci identified in this study provide opportunities to compare allele frequency patterns in multiple M. galloprovincialis populations to determine whether genes under selection for species divergence (identified in this study) are also important for local adaptation within species. Sequence data can also be used in combination with computational approaches to investigate how specific amino acid substitutions affect three‐dimensional protein structure and thermal stability, or whether these sites comprise binding regions undergoing large conformational changes during catalysis (e.g., Fields, Dong, Meng, & Somero, ; Fields et al, ; Liao et al, ; Saarman, Kober, Simison, & Pogson, ). Such data would allow a more direct assessment of the contributions of thermal selection on the evolution of species characteristics mediating present‐day distribution limits.…”
Section: Discussionmentioning
confidence: 99%
“…The conformational changes essential for catalytic function are also well understood, which facilitates structure-function analyses (6). Moreover, our recent work has identified regions of the protein that are key for establishing the appropriate levels of conformational flexibility, to allow the mobile regions (MRs) of the protein to undergo the changes in conformation that are essential for ligand binding and catalysis (2,3).…”
Section: Significancementioning
confidence: 99%
“…One involved conventional site-directed mutagenesis (SDM) followed by enzyme isolation and in vitro characterization of protein stability (rate of heat denaturation) and function (K M NADH ). The second mutagenesis technique involved MDS approaches (3). We used this in silico method to study the effects of the same substitution used in SDM on the overall structural flexibility (rmsd in backbone atom position) and residue-specific flexibility [rms fluctuation (rmsf)] of the protein.…”
mentioning
confidence: 99%
“…Notably, positive alpha/DoS values were identified for the thermotolerance candidate gene cMDH, corroborating that the observed amino acid differences between M. trossulus and M. galloprovincialis are likely adaptive (Fields et al 2006; Table 2-2). cMDH has been implicated, through biochemical studies, as a genetic candidate for setting species-specific thermal limits in Mytilus mussels and other marine mollusks (Mytilus mussels, Fields et al 2006; Lottia limpets, Dong and Somero 2008;Liao et al 2017). Post hoc inspections of cMDH intraspecific read alignments revealed that M. edulis is polymorphic for valine and asparagine amino acids at the functional codon 114, while M.…”
Section: Thermotolerance Candidate Genes and Gene Ontology Enrichmentmentioning
confidence: 99%
“…Determining the adaptive significance of candidate proteins and potential contributions to biological invasions, however, will require functional validation and comparative analyses of thermal physiology between species and populations before strong conclusions can be made (Dean and Thornton 2007). Sequence data can be used in combination with computational approaches to test hypotheses about how specific amino acid substitutions affect three-dimensional protein structure and thermal stability, or whether these sites comprise binding regions undergoing large conformational changes during catalysis (e.g., Fields et al 2012;Fields et al 2015;Liao et al 2017;Saarman et al 2017). Such data will have important implications for understanding the evolution of invasive characteristics that may be favoured under warming ocean conditions (Tepolt 2015).…”
Section: Genetics Of Species Divergence and Implications For Thermal mentioning
confidence: 99%